ATENA–A Novel Rapidly Manufactured Medical Invasive Ventilator Designed as a Response to the COVID-19 Pandemic: Testing Protocol, Safety, and Performance Validation - Rebelo, Tiago; Neutel, Elizabete; Alves, Eurico Castro; Barros, Francisco; Oliveira, Hélder; Machado, Humberto; Mendonça, Joana; Araújo, João Fortuna; Luís, João; Pêgo, José M.; Silva, José; Oliveira, Manuel; et al. (Frontiers in Medicine, 2021)
Background: The urgent need for mechanical ventilators to support respiratory insufficiency due to Sars-Cov-2 led to a worldwide effort to develop low-cost, easily, and locally manufactured ventilators. The ATENA ventilator project was developed in a community-based approach targeting the development, prototyping, testing, and decentralized manufacturing of a new mechanical ventilator. Objective: This article aims to demonstrate ATENA’s adequate performance and safety for clinical use. Material: ATENA is a low-cost ventilator that can be rapidly manufactured, easily assembled, and locally produced anywhere in the world. It was developed following the guidelines and requirements provided by European and International Regulatory Authorities (MHRA, ISO 86201) and National Authorities (INFARMED). The device was thoroughly tested using laboratory lung simulators and animal models. Results: The device meets all the regulatory requirements for pandemic ventilators. Additionally, the preclinical experiences demonstrated security and adequate ventilation and oxygenation, in vivo. Conclusion: The ATENA ventilator had a good performance in required tests in laboratory scenarios and preclinical studies. In a pandemic context, ATENA is perfectly suited for safely treating patients in need of mechanical ventilation.